Common Core Accounting Syllabus for Universities - World Bank Group (World Bank, Washington, DC, 2019)
Strengthening Auditing and Reporting in the Countries of the Eastern Partnership (STAREP) is a regional program of the Centre for Financial Reporting Reform (CFRR). The program aims to create a transparent policy environment and effective institutional framework for corporate reporting within the countries that make up the European Union’s Eastern Partnership: Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine. STAREP’s focus is on the improvement of corporate financial reporting frameworks and their effective implementation. As many countries move towards the adoption of international and regional standards in accounting and auditing, there is a need to ensure high quality, relevant education both for those entering the profession and for ongoing professional development throughout their career. The World Bank’s Accounting and Auditing Education Community of Practice (EduCoP) has enabled shared and peer learning, supporting national efforts to develop accounting and auditing education capacity.